Design of Dental Clinic Medical Record Form at a Community Health Center - Yuliastin, Shafira; Alfiansyah, Gamasiano; Wijayanti, Rossalina Adi; Vestine, Veronika (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Dental medical records are essential documents in dental healthcare services, as they contain comprehensive information regarding patients’ medical conditions and all treatments provided. Several studies indicate that dental clinics commonly use general outpatient forms rather than specific dental medical record forms. This study aimed to design a dental medical record form that can be implemented in healthcare services to achieve standardization in dental documentation. This study employed a literature review method, selecting 27 articles based on predefined inclusion criteria. In designing the dental medical record form, the researchers considered user needs identified in previous studies and developed the form in accordance with form design principles and the 2015 Dental Medical Record Guidelines. The results of this study present a dental medical record form design based on three aspects: physical, anatomical, and content aspects. The physical aspect includes paper material (80 gsm HVS paper), size (F4), shape (portrait-oriented rectangular format), and color (white paper with black ink). The anatomical aspect consists of components such as the heading (including title, form identification, date of issue, and issuance number), introduction, instructions, body, and closing section. The content aspect includes patient identity, odontogram, treatment table, and supporting attachments. This study suggests that the developed dental medical record form design may be considered for implementation in dental clinics at community health centers to enhance the completeness and standardization of patient medical record information.Keywords: form design; medical record; dental medical record